ENVIRONMENTAL QUALITY AND POVERTY ASSESSMENT IN INDONESIA - Kartiasih, Fitri; Pribadi, Wanda (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2020)
Poverty is both a cause and a victim of deteriorating environmental quality. The poor are regarded as very dependent on the environment and natural resources in sustaining their lives so that the environment and natural resources are exploited regardless of their sustainability. On the other hand, environmental degradation causes the poor to get out of poverty. This study aims to (1) analyze the general picture of environmental quality and poverty, (2) analyze the effect of poverty on the environment, (3) analyze the effect of environmental quality on poverty along with other supporting factors in Indonesia 2012-2014. The analytical method used is simultaneous equation with EC2SLS method. The results show that poverty can affect environmental degradation but not vice versa. Exogenous variables that significantly affect the quality of the environment are the growth of the number of poor, economic growth, population density, and literacy rate. Exogenous variables that have significant effect on poverty are economic growth, wage, population density, and literacy rate.